2015
DOI: 10.1007/s40864-015-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception of Driverless Trains

Abstract: The global trend for rail automation is increasing but there are very few publications on public perception of the ongoing changes in the railways. In order to fill this gap and to better understand people's perception of driverless trains, the paper focuses on automation of metro systems with a particular interest in unattended train operation (UTO). A survey seeking a public opinion on UTO was conducted, and the results show that 93 % of female and 72 % of male respondents think that a ''fake'' driver room s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…In contrast, autonomous cars will, in theory, be moving amongst other road users along public routes, thus their interactions with people will be, and may be perceived to be, more complex. Some surveys have been conducted in recent years on the public's perception of autonomous cars, but have typically focused on people as users that does (Fraszczyk et al, 2015) found that the majority of participants were not worried about using a driverless train. This generally positive attitude is reflected in other, non-scientific collections of public opinion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, autonomous cars will, in theory, be moving amongst other road users along public routes, thus their interactions with people will be, and may be perceived to be, more complex. Some surveys have been conducted in recent years on the public's perception of autonomous cars, but have typically focused on people as users that does (Fraszczyk et al, 2015) found that the majority of participants were not worried about using a driverless train. This generally positive attitude is reflected in other, non-scientific collections of public opinion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As an outcome a number of papers with students' input have been written and published in scientific journals or presented at conferences (e.g. Fraszczyk et al, 2015a;Fraszczyk et al, 2015b;Fraszczyk et al, 2016). While being on a placement, students apply their Maths knowledge, but also improve their rail competences and soft skills, including teamwork and work ethics.…”
Section: Social Mediamentioning
confidence: 99%
“…The costs of the control and safety systems are higher when human drivers are no longer present, and can prevent the viability of a given project. In addition, the opposition of some passengers and staff to automation can also be a formidable obstacle [30,31]. The following sub-sections consider these benefits and obstacles in more detail in the context of the Tyne and Wear Metro case study.…”
Section: Overviewmentioning
confidence: 99%
“…Public attitudes towards driverless operation are currently mixed [31], with some passengers worried about the safety of trains controlled automatically and without direct human supervision. Removing potential human errors, together with the additional safety measures highlighted in Sect.…”
Section: Public Attitudes and Staff Oppositionmentioning
confidence: 99%